Two new species of crane fly (Diptera: Limoniidae) from Tasmania, Australia - Billingham, Zacariah D.; Theischinger, Gunther; Levesque-Beaudin, Valerie (Zootaxa, 2023)
Two new species of Australian crane fly are described, illustrated and with COI sequences included: Gynoplistia (Gynoplistia) lutruwita Billingham & Theischinger sp. nov., and Molophilus (Molophilus) serricauda Billingham & Theischinger sp. nov., both from the Huon Valley region of southern Tasmania. Their affinities with other known Australian species are discussed.